2020
DOI: 10.1177/1461348420979468
|View full text |Cite
|
Sign up to set email alerts
|

Coupling resonance mechanism of interfacial stratification of sandwich plate structures excited by SH waves

Abstract: For interfacial stratification mechanism of sandwich plate structures, the forced propagation solution of interface shear stress excited by SH waves is derived by global matrix methods and integral transformation methods. The necessary condition of interfacial shear delamination excited by alternating stress is analyzed with the interface fatigue failure theory. The exact value of forced propagation solution is calculated by adaptive Gauss–Kronrod quadrature numerical integration methods, which is verified via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(118 reference statements)
0
0
0
Order By: Relevance
“…Then, it is proved by the finite element method that the interfacial shear stress directly leads to interfacial delamination [32][33][34][35][36][37][38][39][40][41][42][43][44]. Furthermore, it is found that the interfacial shear stress of double layer structures, sandwich structures, and thin internal layer structures excited by the horizontal shear wave has coupling resonance characteristics [45][46][47]. Coating structures have widely existed in the field of industrial technology [48].…”
Section: Introductionmentioning
confidence: 99%
“…Then, it is proved by the finite element method that the interfacial shear stress directly leads to interfacial delamination [32][33][34][35][36][37][38][39][40][41][42][43][44]. Furthermore, it is found that the interfacial shear stress of double layer structures, sandwich structures, and thin internal layer structures excited by the horizontal shear wave has coupling resonance characteristics [45][46][47]. Coating structures have widely existed in the field of industrial technology [48].…”
Section: Introductionmentioning
confidence: 99%